Intracellular target delivery of 10-hydroxycamptothecin with solid lipid nanoparticles against multidrug resistance. (21st October 2015) - Liu, Min; Chen, Didi; Wang, Chenxu; Chen, Xunhu; Wen, Zhili; Cao, Yu; He, Hongxuan
Abstract: The main objective of this study was to design a suitable drug delivery system for 10-hydroxycamptothecin (HCPT). In this study, HCPT-loaded solid lipid nanoparticle (HCPT-loaded SLN) was successfully prepared. The HCPT-loaded SLN was characterized by size, entrapment efficiency and drug release manner. The cytotoxicity of HCPT-loaded SLN was assessed in vitro using HepG2/HCPT cells and in vivo utilizing human tumor xenograft nude mouse model. HCPT-loaded SLN indicated the ability to target HepG2/HCPT cells and accumulated higher drug content in HepG2/HCPT cells. HCPT-loaded SLN enhanced the cytotoxicity of HCPT in a concentration-dependent manner. Based on these results, HCPT-loaded SLN suggested being a promising vehicle for liver-targeted drug delivery. Moreover, it can be of clinical interest to overcome multidrug resistance (MDR) effectively.